2013
DOI: 10.1155/2013/696343
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transducer and Activator of Transcription Factor 6 Signaling Contributes to Control Host Lung Pathology but Favors Susceptibility againstToxocara canisInfection

Abstract: Using STAT6−/− BALB/c mice, we have analyzed the role of STAT6-induced Th2 response in determining the outcome of experimental toxocariasis caused by embryonated eggs of the helminth parasite Toxocara canis. Following T. canis infection wild-type BALB/c mice developed a strong Th2-like response, produced high levels of IgG1, IgE, and IL-4, recruited alternatively activated macrophages, and displayed a moderate pathology in the lungs; however, they harbored heavy parasite loads in different tissues. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…This work confirms previous observations that in the experimental model of murine toxocariasis infection induces a strong Th-2-like response with increased IL-10 and TGF-β production (Kuroda et al 2001 ; Fan et al 2004 ; Wu et al 2008 ; Faz-López et al 2013 ). We also report that despite the presence of IL-6 and TGF-β which are key cytokines in Th17 differentiation (Basso et al 2009 ), this type of immune response is not induced during T. canis infection in mice.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…This work confirms previous observations that in the experimental model of murine toxocariasis infection induces a strong Th-2-like response with increased IL-10 and TGF-β production (Kuroda et al 2001 ; Fan et al 2004 ; Wu et al 2008 ; Faz-López et al 2013 ). We also report that despite the presence of IL-6 and TGF-β which are key cytokines in Th17 differentiation (Basso et al 2009 ), this type of immune response is not induced during T. canis infection in mice.…”
Section: Introductionsupporting
confidence: 91%
“…T. canis larvae induce strong Th2 response with IL-4 and IL-5 production (Inuo et al 1995 ; Lin et al 2008 ; Malheiro et al 2008 ; Faz-López et al 2013 ), but regulatory cytokines are also produced (Kuroda et al 2001 ; Fan et al 2004 ; Malheiro et al 2008 ). Th1 response is strongly inhibited, as production of IFN-γ and IL-12 is reduced (Kuroda et al 2001 ; Malheiro et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another novel finding was that the immune response in STAT6 −/− mice drove the clearance of the T. canis larvae. Previously, we reported corroborating data on parasite burden and concluded that IgE production was not essential for parasite neutralization because STAT6 −/− mice did not produce IgE [24]. A possible mechanism underlying the resistance to this parasitic infection in STAT6 −/− mice is increased activation of M1 macrophages, which favors iNOS expression.…”
Section: Discussionsupporting
confidence: 76%
“…Previously, we reported that Th2 cytokines have a dual role during toxocariasis. On the one hand, STAT6 activation contributes to host susceptibility, and, alternatively, the down-regulated immune response reduces the immunopathology induced by T. canis infection in the lungs [24].…”
Section: Introductionmentioning
confidence: 99%
“…Isolation and embryonation of eggs were performed as follows: female worms were dissected and from the uterus, eggs were isolated and placed into distilled water; then the mixture was centrifuged 2 times for 10 min at 2,000 g in a solution of NaHCl at 1%. After removal of the supernatant, the sediment was washed 2 times in distilled water and placed into the solution of 0.1 N H 2 SO 4 in tissue flasks at 28˚C for 1 month with gentle daily agitation until the end of embryonation which was controlled under the microscope [ 8 ].…”
Section: Methodsmentioning
confidence: 99%